Local Translation Across Neural Development: A Focus on Radial Glial Cells, Axons, and Synaptogenesis - Agrawal, Manasi; Welshhans, Kristy (Frontiers in Molecular Neuroscience, 2021)
In the past two decades, significant progress has been made in our understanding of mRNA localization and translation at distal sites in axons and dendrites. The existing literature shows that local translation is regulated in a temporally and spatially restricted manner and is critical throughout embryonic and post-embryonic life. Here, recent key findings about mRNA localization and local translation across the various stages of neural development, including neurogenesis, axon development, and synaptogenesis, are reviewed. In the early stages of development, mRNAs are localized and locally translated in the endfeet of radial glial cells, but much is still unexplored about their functional significance. Recent in vitro and in vivo studies have provided new information about the specific mechanisms regulating local translation during axon development, including growth cone guidance and axon branching. Later in development, localization and translation of mRNAs help mediate the major structural and functional changes that occur in the axon during synaptogenesis. Clinically, changes in local translation across all stages of neural development have important implications for understanding the etiology of several neurological disorders. Herein, local translation and mechanisms regulating this process across developmental stages are compared and discussed in the context of function and dysfunction.